THE EVOLVING ROLE OF NON-PROFIT ORGANIZATIONS IN SHAPING SOCIETY - Qodirova Mamlakat Muminovna (American Journals, 2024)
Non-profit organizations (NPOs) have long played a vital role in addressing societal challenges and fostering positive change. In the current landscape, these organizations are increasingly recognized as key players in the organization and transformation of society. This article examines the evolving role of NPOs and their significance in the contemporary social, economic, and political landscape. It delves into the various ways in which NPOs contribute to the organization of society, including their involvement in service provision, advocacy, community empowerment, and collaborative initiatives. The article also explores the unique strengths and limitations of NPOs, as well as the emerging trends and challenges that shape their evolving role. Drawing on empirical research and theoretical perspectives, this study provides a comprehensive understanding of the multifaceted impact of NPOs in the organization of society, offering insights for policymakers, practitioners, and scholars interested in the intersection of the non-profit sector and societal development.
Keywords: Non-profit organizations (NPOs), Societal organization and transformation, Service provision, Advocacy and social change, Community empowerment, Collaborative initiatives, Strengths and limitations of NPOs